2017
DOI: 10.3389/fneur.2017.00474
|View full text |Cite
|
Sign up to set email alerts
|

Difference in the Inhibitory Effect of Temozolomide on TJ905 Glioma Cells and Stem Cells

Abstract: This study aims to determine the difference in the inhibitory effect of temozolomide (TMZ) on TJ905 glioma cells and stem cells. TJ905 cancer stem cells were isolated. Livin is a member of the inhibitor of apoptosis protein family. The TJ905 cells and cancer stem cells were transfected with a Livin-shRNA and negative-shRNA, respectively, and then treated with TMZ. At 48 h post-transfection, a cell counting kit 8 assay, flow cytometry, and real-time qPCR were performed to detect cell proliferation, the cell cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…The results showed that TMZ effectively attenuated the duplication and cell cycle of glioma cells and stem cells in a dose‐dependent manner and had a greater effect on U87 cells and U251 cells, which revealed the presence of different resistant mechanism in glioma cells and glioma stem cells. Consistently, the suppressive effect of TMZ on TJ905 glioma cells was more significant than its effect on TJ905 stem cells . And Beier et al also discovered that glioblastoma stem cell had stronger resistance to TMZ compared with glioblastoma cells …”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The results showed that TMZ effectively attenuated the duplication and cell cycle of glioma cells and stem cells in a dose‐dependent manner and had a greater effect on U87 cells and U251 cells, which revealed the presence of different resistant mechanism in glioma cells and glioma stem cells. Consistently, the suppressive effect of TMZ on TJ905 glioma cells was more significant than its effect on TJ905 stem cells . And Beier et al also discovered that glioblastoma stem cell had stronger resistance to TMZ compared with glioblastoma cells …”
Section: Discussionmentioning
confidence: 89%
“…Consistently, the suppressive effect of TMZ on TJ905 glioma cells was more significant than its effect on TJ905 stem cells. 18 And Beier et al also discovered that glioblastoma stem cell had stronger resistance to TMZ compared with glioblastoma cells. 4 Relevant studies have revealed the PLK1 was involved in the mechanism of cancer growth.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure was carried out as previously described ( Jin et al, 2017 ). The total RNA was isolated from RAW264.7 cells or liver tissues using TRIzol reagent (Takara, Dalian, China).…”
Section: Methodsmentioning
confidence: 99%
“…The procedure was conducted as described previously by our group (Jin et al, 2017). Lentiviral vectors for TLR3 and a negative control were constructed by Tuojie (Wuhan, China).…”
Section: Methodsmentioning
confidence: 99%